WHAT A KRAB! SMALL TALKS FOR COMEDIC PURPOSES AMONG KRUSTY KRAB'S STAFFS AND CUSTOMERS IN SPONGEBOB SQUAREPANTS - Allauna Lila Ihzanda; Wulan Permata Sari; Lesti Widiyawati (IAIN Surakarta, 2026)
Small talk is commonly understood as a form of phatic communication that maintains social relationships rather than conveying essential information. This study re-examines its role in generating humor, showing how it fosters closeness among characters and refreshes conversational dynamics. Drawing on the concept of phatic communion and supporting theoretical perspectives, the research analyzes verbal and nonverbal elements in everyday interactions within The SpongeBob SquarePants Movie: Sponge on the Run (2020). The findings indicate that gestures and small talk contribute to humor in spontaneous exchanges while reinforcing social bonds. Moreover, the study highlights how exaggerated body movements and explicit verbal expressions serve as mechanisms for building social closeness and producing humor in the film. Future research could expand this study by comparing the use of small talk in other animated series or in real-life interactions. This would provide a broader understanding of how humor functions in everyday communication.